Ø¹Ù†Ø§ÙŠØ© Ø§Ù„Ù…ØºØ§Ø±Ø¨Ø© Ø¨Ø§Ù„Ø³ÙŠØ±Ø© Ø§Ù„Ù†Ø¨ÙˆÙŠØ© (ÙƒØªØ§Ø¨ Ø§Ù„Ø´Ù…Ø§Ø¦Ù„ Ø£Ù†Ù…ÙˆØ°Ø¬Ù‹Ø§) - Murad Zahwi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to find out how the Moroccan community pays attention to the sirah nabawiyyah, specifically in the book of al-SyamÄ'il al-Muá¸¥ammadiyyah. This study uses a qualitative method with a descriptive analytical and historical approach. The results showed that among the forms of Moroccan people's attention to the sirah of the Prophet Muhammad especially the book of al-SyamÄ'il al-Muá¸¥ammadiyyah is the number of syurÅ«á¸¥ (explanations) of the Moroccans to the book of al-SyamÄ'il al-Muá¸¥ammadiyyah as evidence of their attention to the book. The book of al-SyamÄ'il al-Muá¸¥ammadiyyah by al-TirmiÅ¼Ä« is one of the most important references to get to know the figure of the Prophet because it has contained everything related to his character, character and physical. Al-TirmiÅ¼Ä« strongly maintains the validity of the hadith and is committed to the validity of the hadith he narrates